Circulating FGF21 is lower in South Asians compared with Europids with type 2 diabetes mellitus - Carlijn A Hoekx; Borja Martinez-Tellez; Maaike E Straat; Maurice B Bizino; Huub J van Eyk; Hildebrandus J Lamb; Johannes W A Smit; Ingrid M Jazet; Kimberly J Nahon; Laura G M Janssen; Patrick C N Rensen; Mariëtte R Boon (Endocrine Connections)
Objective: Inflammation contributes to the development of type 2 diabetes mellitus (T2DM). While South Asians are more prone to develop T2DM than Europids, the inflammatory phenotype of the South Asian population remains relatively unknown. Therefore, we aimed to investigate potential differences in circulating levels of inflammation-related proteins in South Asians compared with Europids with T2DM. Method: In this secondary analysis of three randomized controlled trials, relative plasma levels of 73 inflammation-related proteins were measured using an Olink Target Inflammation panel and the serum fibroblast growth factor 21 (FGF21) concentration using an ELISA kit in Dutch South Asians (n = 47) and Dutch Europids (n = 49) with T2DM. Results: Of the 73 inflammation-related proteins, the relative plasma levels of six proteins were higher (stem cell factor, caspase-8, C–C motif chemokine ligand 28, interferon-gamma, sulfotransferase 1A1 and cystatin D; q-value <0.05), while relative levels of six proteins were lower (FGF21, human fibroblast collagenase, interferon-8, C–C motif chemokine ligand 4, C–X–C motif chemokine ligand 6 and monocyte chemoattractant protein-1; q-value <0.05) in South Asians compared with Europids. Of these, the effect size of FGF21 was the largest, particularly in females. We validated this finding by assessing the FGF21 concentration in serum. The FGF21 concentration was indeed lower in South Asians compared with Europids with T2DM in both males (−42.2%; P < 0.05) and females (−58.5%; P < 0.001). Conclusion: Relative plasma levels of 12 inflammation-related proteins differed between South Asians and Europids with T2DM, with a significantly pronounced reduction in FGF21. In addition, the serum FGF21 concentration was significantly lower in South Asian males and females compared with Europids. Whether low FGF21 is an underlying cause or consequence of T2DM in South Asians remains to be determined. Clinical trial registration: ClinicalTrials.gov (NCT01761318, registration date 20-12-2012; NCT02660047, registration date 21-03-2018; and NCT03012113, registration date 06-01-2017).